2009
DOI: 10.1139/h08-104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of presurgical exercise training on systemic inflammatory markers among patients with malignant lung lesions

Abstract: Systemic inflammation plays an important role in the initiation, promotion, and progression of lung carcinogenesis. The effects of interventions to lower inflammation have not been explored. Accordingly, we conducted a pilot study to explore the effects of exercise training on changes in biomarkers of systemic inflammation among patients with malignant lung lesions. Using a single-group design, 12 patients with suspected operable lung cancer were provided with structured exercise training until surgical resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 17 publications
1
48
0
2
Order By: Relevance
“…Since the early trials, numerous studies have found that interval training provides benefits for a number of cancer survivors, including those receiving chemotherapy 38 or stem-cell transplantation 52 , those with anemia (hemoglobin: 80-110 g/L) 53 , and those awaiting lung resection for non-small-cell lung cancer 54 . Dimeo et al 55 examined the effect of an in-hospital interval-training program for patients with a mix of cancers (n = 70) undergoing highdose chemotherapy and autologous peripheral stem-cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early trials, numerous studies have found that interval training provides benefits for a number of cancer survivors, including those receiving chemotherapy 38 or stem-cell transplantation 52 , those with anemia (hemoglobin: 80-110 g/L) 53 , and those awaiting lung resection for non-small-cell lung cancer 54 . Dimeo et al 55 examined the effect of an in-hospital interval-training program for patients with a mix of cancers (n = 70) undergoing highdose chemotherapy and autologous peripheral stem-cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…An important remaining question is whether surgery should be postponed to allow for prehabilitation. Studies have demonstrated that the moderate delays in treatment for non-small-cell lung cancer patients are not associated with worsened long-term prognosis [39,40], and postponing surgery for long enough to reach pre-operative fitness targets may improve postoperative risk profiles [6]. However, this issue has not been studied formally in RCTs or across other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Out of a maximum score of 6 (higher scores indicate lower risk of bias), one study achieved a score of 6 [31], three studies achieved a score of 4 [13,25,26], seven studies achieved a score of 3 [14,16,18,20,24,27,33], four studies achieved a score of 2 [21,40], three studies achieved a score of 1 [15,17,23], and three studies achieved a score of 0 [19,29,32].…”
Section: Risk Of Biasmentioning
confidence: 99%
“…The results indicated that exercise training resulted in a signifi cant reduction in ICAM-1 (P = 0.041), a cell surface glycoprotein essential for controlling cell migration, cancer cell invasion, and metastasis. Change in exercise capacity was not associated with change in systemic infl ammatory markers [29].…”
Section: Exercise Therapy Following a Lung Cancer Diagnosismentioning
confidence: 79%